Quantum Biophysics: Exploring the Role of Quantum Mechanics in Biological Processes - Al Hamdaney, Nadia Adel Saeed Khaleel; Al Kuyani, Iman Amin Ahmed; Al-Nafouli, Bakr Khaled Abdul Ghani Yahya; Al-Obaidi, Obaida Khader Ibrahim Kulaib; Ghanem, Zainab Thaer (American Journal of Botany and Bioengineering, 2025)
The role of quantum mechanics in biological processes is examined. Experimental results show that quantum superposition and entanglement are functioning also in biological systems. A spectrum of emerging quantum biophysics reveals the reasons why they have been overlooked for such a long time since nature seems to be prepared for a seamless unification of the described world. What explains these formal findings, and what can come averagely out of this knowledge for biology and biotechnology? Biological systems, ‘machines’, and processes work undeniably best under ambient conditions. As a result, there is a well-established stance treated throughout the history of modern Science, and of physics in particular, to consider non-classical solutions and quantum effects significant only from inertial scales. But can these general statements be confirmed analytically for magnitude as large as cells, DNA chains, or even on low-density laser-cooled atoms or molecules? From investigating laser light plus cold atom-molecule experiments, living systems, and especially biological organisms might emerge as truly astounding quantum machines. This comprises already established quantum biophysics near fields and lasers at sub-bio scales along with manipulations of single molecules. Relying on the rudiments of quantum theory developed a century ago, quantum mechanics has successfully reconstructed a sequence of experiments and opened up dimensions far beyond a spiration. There exists a virtual unbounded domain of far less recognized yet increasingly powerful quantum formalism where quantum biophysics may straddle an entirely novel frontier between physics and life sciences. The present study makes an effort to fleet some light at the frontiers of quantum/classical on non-inertial laboratory-biological bridges on the way towards a rigorous unification of quantum mechanics and bio processes. For this purpose, the interplay of recent investigations in atom optics and tissue optics is scrutinized. A brief resume of experiments on laser irradiated DNA plasmids testifies the aggregate complexity, optimalization, flexibility, and well reserve of charge/storage capacity of double-helix symmetry. On the other hand, there has been a slump of woodworking results proving the contested stability of even larger unrelated biomolecules. Conjecture the operative structural styles through steady-state refracted coherence trapping, biostatistical populations and cellular/experimental targets are largely partitioned.